Methylglyoxal further impairs adipose tissue metabolism after partial decrease of blood supply. (11th July 2013) - Rodrigues, Tiago; Matafome, Paulo; Seiça, Raquel
Abstract: We previously showed that methylglyoxal-induced glycation induces adipose tissue lesions, including decreased irrigation and macrophage recruitment, independently of obesity. Here, we developed a model of partially decreased adipose tissue irrigation, a common condition in obese individuals. We aimed to study the role of methylglyoxal in the metabolic adaptations to such conditions 1 and 48 hours after decreased blood supply, avoiding other confoundable variables. Irrigation decrease during 1 hour leaded to increased activation of ERK1/2 and degradation of Ikappa-Balpha and Perilipin A in methylglyoxal-treated normal Wistar rats. After 48 hours, all rats showed increased fasting glycaemia and insulinemia. However, methylglyoxal-treated rats had higher free fatty acids and triglycerides levels and decreased adiponectinemia, consequent to decreased PPARgamma levels in partially irrigated adipose tissue. Our data show that besides causing vascular dysfunction, glycation further contributes to impaired adipocyte metabolism after a decrease of tissue irrigation, what may hamper metabolic adaptation during tissue expansion.